2008
DOI: 10.1590/s0103-84782008000200003
|View full text |Cite
|
Sign up to set email alerts
|

Tamanho ótimo de parcela para ensaios com sorgo granífero em duas épocas de semeadura

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
1
9
0
2
Order By: Relevance
“…Table 4 shows values for the estimates of d in accordance with the pre-established conditions. Analysing this table, significant decreases can be seen in the values of d (gains in experimental precision) with increases in the size of small plots, although this increase in precision is small with additional increases in the area of plots over a certain size limit, agreeing with the results obtained by various authors (BRUM et al, 2008;DONATO et al, 2008;HENRIQUES NETO et al, 2004;LÚCIO et al, 2011;LÚCIO et al, 2012;MARTIN et al, 2004;;SANTOS et al, 2012).…”
Section: Resultssupporting
confidence: 89%
“…Table 4 shows values for the estimates of d in accordance with the pre-established conditions. Analysing this table, significant decreases can be seen in the values of d (gains in experimental precision) with increases in the size of small plots, although this increase in precision is small with additional increases in the area of plots over a certain size limit, agreeing with the results obtained by various authors (BRUM et al, 2008;DONATO et al, 2008;HENRIQUES NETO et al, 2004;LÚCIO et al, 2011;LÚCIO et al, 2012;MARTIN et al, 2004;;SANTOS et al, 2012).…”
Section: Resultssupporting
confidence: 89%
“…Na literatura é comum a obtenção de estimativas do valor de b superiores à unidade (BRUM et al, 2008;LOPES et al, 2005;LORENTZ et al, 2007;LORENTZ et al, 2010;LÚCIO et al, 2011;LÚCIO et al, 2012;MARTIN et al, 2007;OLIVEIRA et al, 2006;SANTOS et al, 2012;STORCK et al, 2006b;STORCK;BISOGNIN;OLIVEIRA, 2006 Através do método de Hatheway (1961), que determina o denominado tamanho conveniente de parcela, estimaram-se vários tamanhos de parcela dentre os quais o pesquisador poderá escolher aquele que melhor lhe convier, a partir de condições experimentais pré-definidas. Na Tabela 2 são apresentados os diferentes tamanhos convenientes de parcelas para avaliação do rendimento de grãos de cultivares de girassol, adotandose um nível de significância de 5% de probabilidade.…”
Section: Resultsunclassified
“…There are several other factors that affect experimental precision, among them: the heterogeneity of the soil, the genetic material, number of environments utilized, sample size, and the management of the experiment (Martin et al, 2005;Storck et al, 2006;Brum et al, 2008;Cargnelutti Filho et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies about experimental precision are reported in the literature in which the cultures utilized were: maize (Martin et al, 2005); sorghum (Brum et al, 2008); potato (Storck et al, 2011); soybean and bean, castor bean, crambe, turnip, rice (Carnelutti Filho et al, 2009, 2010, 2011a,b, 2012; peach . However, Cattapatti et al (2008) reported the only Brazilian study about experimental precision with popcorn, concluding that for pre-harvest traits, one can use 4 repetitions and 5 plants per plot.…”
Section: Introductionmentioning
confidence: 99%